The structural efficiency of tapered steel section with perforation under lateral torsional buckling behaviour - De’nan, Fatimah; Hashim, Nor Salwani; Lim, Cheng Kuan (Multi-Science Publishing, 2020)
Purpose - Tapered section can resist maximum stress at a single location while the stresses are considerably lower at the rest of the member and therefore it could have higher structural efficiency compared to conventional section. It could also satisfy functional requirements while reducing weight and cost in many fields of civil construction. Perforation in the steel section also eases the integration of Mechanical and Electrical (M&E) services such as ventilation pipes and electrical cables within the structural depths of the beam. In this analysis, the structural efficiency of tapered steel section with perforation under lateral-torsional buckling behaviour is investigated.